Defense Limitations of Single Parents in the Biparental Convict Cichlid Fish: A Field Study - Layla Al-Shaer; Brandon Baumann; Murray Itzkowitz (Hydrobiology, 2025)
A field study on the biparental convict cichlids (Amatitlania siquia) in Lake Xiloá, Nicaragua was conducted to understand how the loss of a parent’s parental care affects the antipredator behavior of both parents and offspring during intruder events. We hypothesized that the combined efforts of two parents would result in increased intruder aggression and decreased offspring dispersion compared to single-parents of either sex, and that single-females and males would differ in their ability to deter predators and manage offspring dispersion. Both parents in a pair chased half the intruders that single-females did and the same number as single-males, suggesting that the presence of a partner deters intruders from encroaching and affords parents more time to engage in other parental care duties. Compared to single-parents, offspring accompanied by both parents were seldom left alone and showed greater shoal cohesion—both of which would presumably lower their risk of predation. Although there were sex differences between single-parents in terms of how often they left their offspring unattended and called to them using pelvic fin-flicks, neither sex was found to be more effective at managing the distribution of their offspring. This field study provides empirical evidence to support the need for biparental care in this species and gives insight into the selection pressures shaping parental investment.